Labile Fe(III) from sorbed Fe(II) oxidation is the key intermediate in Fe(II)-catalyzed ferrihydrite transformation - Sheng, Anxu; Juan Liu; Li, Xiaoxu; Qafoku, Odeta; Richard N. Collins; Adele M. Jones; Pearce, Carolyn I; Wang, Chongmin; Ni, Jinren; Lu, Anhuai; Rosso, Kevin M (Geochimica et Cosmochimica Acta, 2020)
Ferrihydrite (Fh) is a major Fe(III)-(oxyhydr)oxide nanomineral distinguished by its poor crystallinity and thermodynamic metastability. While it is well known that in suboxic conditions aqueous Fe(II) rapidly catalyzes Fh transformation to more stable crystalline Fe(III) phases such as lepidocrocite (Lp) and goethite (Gt), because of the low solubility of Fe(III) the mass transfer pathways enabling these rapid transformations have remained unclear for decades. Here, using a selective extractant, we isolated and quantified a critical labile Fe(III) species, one that is more reactive than Fe(III) in Fh, formed by the oxidation of aqueous Fe(II) on the Fh surface. Experiments that compared time-dependent concentrations of solid-associated Fe(II) and this labile Fe(III) against the kinetics of phase transformation showed that its accumulation is directly related to Lp/Gt formation in a manner consistent with the classical nucleation theory. 57Fe isotope tracer experiments confirm the oxidized Fe(II) origin of labile Fe(III). The transformation pathway as well as the accelerating effect of Fe(II) can now all be explained on a unified basis of the kinetics of Fe(III) olation and oxolation reactions necessary to nucleate and sustain growth of Lp/Gt products, rates of which are greatly accelerated by labile Fe(III).
Keywords: Fe(II)-catalyzed transformation of ferrihydrite; Olation and oxolation of intermediates; pH effect; Quantification of intermediate Fe(III) species